OWNER/MANAGEMENT CHARACTERISTICS, BUSINESS CHARACTERISTICS, AND BUSINESS DECISION-MAKING - Antonius Singgih Setiawan; Delfi Panjaitan (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
Business decision-making is a crucial point in business activities. Therefore, this study aims to examine whether management characteristics, the ability to see opportunities, and the ability to improvise positively impact business decision-making. This study used a sample of 118 (78.7%) businessmen respondents in Palembang City. The research hypothesis was tested using Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis with Warp PLS software version 5.0. The results of this study show that management characteristics, the ability to see opportunities, and the ability to improvise positively affect firms' business decision-making in Palembang City.